Ray-optics cloaking devices for large objects in incoherent natural light - Chen, Hongsheng (2013)
A cloak that can hide living creatures from sight is a common feature of mythology but still remains unrealized as a practical device. To preserve the wave phase, the previous cloaking solution proposed by Pendry and colleagues required transformation of the electromagnetic space around the hidden object in such a way that the rays bending around the object inside the cloak region have to travel faster than those passing it by. This difficult phase preservation requirement is the main obstacle for building a broadband polarization-insensitive cloak for large objects. Here we propose a simplified version of Pendry’s cloak by abolishing the requirement for phase preservation, as it is irrelevant for observation using incoherent natural light with human eyes, which are phase and polarization insensitive. This allows for a cloak design on large scales using commonly available materials. We successfully demonstrate the cloaking of living creatures, a cat and a fish, from the eye.